1998
DOI: 10.1002/(sici)1099-1573(19980201)12:1<70::aid-ptr189>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility ofEntamoeba histolytica andGiardia lamblia to some medicinal plants used by the people of Southern Mexico

Abstract: The antiprotozoal properties of six medicinal plants, used by the people of Southern Mexico to treat diarrhoea, were evaluated in vitroagainst Entamoeba histolyticaand Giardia lambliatrophozoites, the most active being the methanol extracts of Rubus coriifolius, Cuphea pinetorumand Helianthemum glomeratum. Further activity guided fractionation of Cuphea pinetorumroots extract led to the isolation of kaempferol and quercetin as the active principles. © 1998 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…In this sense, from the species Geranium mexicanum HBK (Geraniaceae), Cuphea pinetorum Benth (Litraceae), Helianthemum glomeratum Lag. (Cistaceae), and Rubus coriifolius Focke (Rosaceae), compounds with in vitro antigiardial properties have been isolated, these compounds were identified as flavonoids kaempferol, tiliroside and (−)-epicatechin (Calzada et al, 1998(Calzada et al, , 1999Alanís et al, 2003;Calzada, 2005 Flavonoids have been reported to exert multiple biological effects due to their antioxidant and free radical-scavenging abilities; although results from different studies have demonstrated that flavonoids can act as pro-oxidant at very high doses. Furthermore most investigations have reported antibacterial, antifungal, antiviral, anti-inflammatory, anti-allergic activity and protective roles in heart diseases, cancer and different pathologies (Martínez et al, 2002;Matsuda et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, from the species Geranium mexicanum HBK (Geraniaceae), Cuphea pinetorum Benth (Litraceae), Helianthemum glomeratum Lag. (Cistaceae), and Rubus coriifolius Focke (Rosaceae), compounds with in vitro antigiardial properties have been isolated, these compounds were identified as flavonoids kaempferol, tiliroside and (−)-epicatechin (Calzada et al, 1998(Calzada et al, , 1999Alanís et al, 2003;Calzada, 2005 Flavonoids have been reported to exert multiple biological effects due to their antioxidant and free radical-scavenging abilities; although results from different studies have demonstrated that flavonoids can act as pro-oxidant at very high doses. Furthermore most investigations have reported antibacterial, antifungal, antiviral, anti-inflammatory, anti-allergic activity and protective roles in heart diseases, cancer and different pathologies (Martínez et al, 2002;Matsuda et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Because of its popularity, pharmacological and phytochemical studies have been conducted by Calzada and collaborators since 1995 on H. glomeratum collected in the State of Chiapas. Briefly, methanol extracts of the aerial parts of H. glomeratum had antibacterial, antifungal and antiprotozoal properties 1997;Calzada et al, 1998a). In relation to phytochemical studies, three flavonoids (kaempferol, quercetin and tiliroside) were isolated from the aerial parts, with lethality against brine shrimp as well as antiamoebic activity (Calzada et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the current study was conducted to evaluate the in vitro anti-giardia activity of hexanic extract of lima and some of its constituents. However, several plants have been used as anti-giardia remedy, with positive results, among others: Rubus coriifolius, Cuphea pinetorum and Helianthemum glomeratum (Calzada et al, 1998) On the other hand, it is known that the potency of lime extracts is enhanced by the type of solvent used, indicating that there are some active ingredients in lime which have high antimicrobial/antifungal effect but which would not be released except when lime fruit is used in conjunction with a particular solvent (Taylor, 2004). For the present work, we choose hexane in accordance with previous antimicrobial results (Camacho-Corona et al, 2008; Sandoval-Montemayor et al, 2012).…”
Section: Discussionmentioning
confidence: 99%